Transgenerational endocrine disruption: Does elemental pollution affect egg or nestling thyroid hormone levels in a wild songbird? - Ruuskanen Suvi; Espín Silvia; Sanchéz-Virosta Pablo; Sarraude Tom; Hsu Bi-Yan; Pajunen Piia; Costa Rute A.; Eens Marcel; Hargitai Rita; Török János; Eeva Tapio (ELSEVIER SCI LTD, 2022)
Endocrine disrupting chemicals (EDCs) include a wide array of pollutants, such as some metals and other toxic elements, which may cause changes in hormonal homeostasis. In addition to affecting physiology of individuals directly, EDCs may alter the transfer of maternal hormones to offspring, i.e. causing trans-generational endocrine disruption. However, such effects have been rarely studied, especially in wild populations. We studied the associations between environmental elemental pollution (As, Cd, Cu, Ni, Pb) and maternally-derived egg thyroid hormones (THs) as well as nestling THs in great tits (Parus major) using extensive sampling of four pairs of polluted and reference populations across Europe (Finland, Belgium, Hungary, Portugal). Previous studies in these populations showed that breeding success, nestling growth and adult and nestling physiology were altered in polluted zones compared to reference zones. We sampled non-incubated eggs to measure maternally-derived egg THs, measured nestling plasma THs and used nestling faeces for assessing local elemental exposure. We also studied whether the effect of elemental pollution on endocrine traits is dependent on calcium (Ca) availability (faecal Ca as a proxy) as low Ca increases toxicity of some elements. Birds in the polluted zones were exposed to markedly higher levels of toxic elements than in reference zones at the populations in Finland, Belgium and Hungary. In contrast to our predictions, we did not find any associations between overall elemental pollution, or individual element concentrations and egg TH and nestling plasma TH levels. However, we found some indication that the effect of metals (Cd and Cu) on egg THs is dependent on Ca availability. In summary, our results suggest that elemental pollution at the studied populations is unlikely to cause overall TH disruption and affect breeding via altered egg or nestling TH levels with the current elemental pollution loads. Associations with Ca availability should be further studied. (C) 2019 Published by Elsevier Ltd.